2021
DOI: 10.1111/ijd.15384
|View full text |Cite
|
Sign up to set email alerts
|

Medical imaging examination in psoriasis and early psoriatic arthritis patients: an updated systematic review and meta‐analysis

Abstract: Psoriatic arthritis appears in one in four skin psoriasis patients. Early detection of the presence of joint involvement and early interception of its developments may minimize long-term functional disability, and the radiological methods may be a perfect choice. To summarize and compare different imaging methods for diagnosing early-stage psoriatic arthritis and determine the necessity of joint examination in all psoriasis patients, several electronic databases, including MEDLINE and EMBASE, were searched for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Early screening with imaging tools such as ultrasonography has been widely cited in clinical practice (1,11,12).Overseas studies have found that psoriasis patients have a signi cantly higher incidence of adhesion point and synovitis under high-frequency ultrasound than normal subjects, and in a cohort study of patients with psoriasis there was a positive correlation between age and active synovitis, whereas the gender was male, and high PASI scores were positively correlated with active adhesion point in ammation (15).In this study, the patients presented with subclinical ultrasound damage mostly in the form of synovitis for the following reasons: rstly, studies have shown that the most frequent sites of tendon telangiectasia in patients with psoriasis when the knee joint and Achilles tendon (20).The highfrequency ultrasound data collected in this study were mostly single-handed Doppler soft-tissue ultrasound, so it was di cult to detect lesions in the Achilles tendon. Moreover, the sample size of this study was limited; therefore, it is more than likely to be biased.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early screening with imaging tools such as ultrasonography has been widely cited in clinical practice (1,11,12).Overseas studies have found that psoriasis patients have a signi cantly higher incidence of adhesion point and synovitis under high-frequency ultrasound than normal subjects, and in a cohort study of patients with psoriasis there was a positive correlation between age and active synovitis, whereas the gender was male, and high PASI scores were positively correlated with active adhesion point in ammation (15).In this study, the patients presented with subclinical ultrasound damage mostly in the form of synovitis for the following reasons: rstly, studies have shown that the most frequent sites of tendon telangiectasia in patients with psoriasis when the knee joint and Achilles tendon (20).The highfrequency ultrasound data collected in this study were mostly single-handed Doppler soft-tissue ultrasound, so it was di cult to detect lesions in the Achilles tendon. Moreover, the sample size of this study was limited; therefore, it is more than likely to be biased.…”
Section: Discussionmentioning
confidence: 99%
“…Imaging tools such as ultrasonography and MRI have also been widely cited in the early screening of PsA (1,11,12).High-frequency ultrasound is an imaging technique for detecting PsA in the subclinical stage by evaluating the skin, nails, joints and attachment points of patients with psoriasis (13).Elevated rates of asymptomatic attachment point in ammation, subclinical synovitis in psoriasis patients compared to normal subjects (14)(15)(16).Patients with psoriasis with joint pain in the prodromal phase had elevated rates of tenosynovitis and adhesion point in ammation compared to patients with psoriasis with cutaneous manifestations only, and patients with psoriasis in the prodromal phase who had adhesion point in ammation on ultrasound could progress to PsA (11).…”
Section: Introductionmentioning
confidence: 99%
“…Thereby, limitations in daily functioning or participation restrictions, that can, apart from disease activity, be related to personal and environmental factors, may thus remain unrecognized. Therefore, there is a need for the development and evaluation of strategies aimed at the early detection of functional disability, its diagnosis and access to appropriate rehabilitation services, as well as on secondary prevention strategies focusing on specific goals for people who can and want to adhere to lifestyle advice and help those who can and want to stay in work [ 61 , 62 , 63 , 64 ]. Regarding the latter, additional education for health professionals delivering lifestyle interventions is likely to be needed, as supporting behavioral changes in patients requires specific professional skills.…”
Section: Discussionmentioning
confidence: 99%
“…Although existing reviews have already pointed out that imaging methods, such as ultrasound and MRI, can also become a valuable method to detect early the inflammatory lesions of joints, the expensive costs of exam fees and related equipment, and the long waiting time are limitations. Examination time and hard-interpreted imaging results for non-professional clinicians were all hurdles that hamper the prevalence of application on imaging examinations on patients with PsC ( 22 , 25 , 102 ). Consequently, a fast exam kit with an accessible kit becomes more necessary, suggesting an imperative need to explore a possible biomarker.…”
Section: Discussionmentioning
confidence: 99%
“…Psoriatic arthropathy, an early stage of joint involvement that may not fulfill the PsA diagnostic criteria, is more common than PsA in PsO patients ( 23 ). For those with asymptomatic joint abnormalities, early synovio-entheseal inflammation or bone erosion can be detected by imaging features like ultrasonography or MRI ( 24 , 25 ). However, with these predictors, it is still hard to foresee the possibility of the transition to PsA ( 26 ).…”
Section: Introductionmentioning
confidence: 99%